Recurrent Vomiting, an Atypical Presentation of Sheehan’s Syndrome (Bangladesh Journal of Medicine, 2023)
Sheehan’s syndrome is a rare condition involving injury to the pituitary gland following excessive blood loss during delivery. Its presentation is too variable sometimes, it may be remained asymptomatic for long times. Here we are presenting a 50 yr-old woman presented with recurrent vomiting admitted in the Rajshahi Medical College Hospital.Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 217